Land use changes associated with the expansion of sugar cane crops and their influences on soil removal in a tropical watershed in São Paulo State (Brazil) - Couto, Antonio Aparecido [UNESP]; da Conceição, Fabiano Tomazini [UNESP]; Fernandes, Alexandre Martins [UNESP]; Spatti, Eder Paulo [UNESP]; Lupinacci, Cenira Maria [UNESP]; Moruzzi, Rodrigo Braga [UNESP] (Elsevier, 2019)
In the last decades, the use of biofuels as a mitigation measure for carbon emissions has led to land use and land cover changes in southeastern Brazil, especially in Paulista Peripheral Depression – Paraná Sedimentary Basin. Considering the human-landscape system associated with energy policy, these changes can affect landscape and natural resources over a range of temporal and special scales. Thus, the aim of study was on how human-landscape interactions have influenced the geomorphological dynamics in a São Paulo region that contains sugar cane crops associated with soils derived from sandstones and mudstones. The use of the Universal Soil Loss Equation (USLE) in three different scenarios from land use changes allowed verifying how they have affected soil loss: natural conditions (savannah), current land use and with the expansion of sugar cane crops. In addition, the total sediment transported, the sediment delivery ratio and the rate of soil removal were measured, considering the current land use. The land use scenarios pointed out that the land use change is directly related to increasing rates of soil loss, i.e. 0.03, 3.5 and 12.6 t ha−1 yr−1 for the natural conditions, current land use and with the expansion of sugar cane crops, respectively. These rates in the current land use and with continuous expansion of sugar cane crops are higher than the tolerable erosion limits in 17 and 57% of the study area, respectively. The suspended sediment concentration increases with increasing Cachoeirinha Stream discharge, with a specific daily flux of 88 kg km−2 day−1. The mean monthly flux in 2014 was 32 t month−1, with varying from 3.1 (August) to 144 (January) t month−1. The wet period was responsible for ca. 90% (436 t) of the total solids transported in 2014. The sediment delivery ratio was 9% of the total soil loss. The current rate of soil removal of 25.8 m Myr−1 is almost 3-fold higher than the long-term denudation rates suggested for the Peripheral Depression (9 m Myr−1). With the continuous expansion of sugar cane crops, the rate of soil removal probably will be higher than that obtained in the current scenario and, consequently, the current denudation rates should increase further. Thus, this study reinforce that the human-landscape systems in São Paulo State associated with energy policy are complex and increase the natural processes of soil removal and, consequently, affect the landscape evolution.
Keywords: Brazil; Energy policy; Human-landscape system; Landscape evolution